Development of a Small Historian Learning Model Based on a Local History Site Surakarta Kasunanan Palace on the Sub-Discussion of the Islamic Kingdom Era in Indonesia Class X MAN 1 Surakarta - Wardayanti, Rosa; Suharso, R; Romadi, Romadi (Universitas Negeri Semarang, 2020)
The objectives of this research are: (1) to analyze the learning condition in X grade before the development of learning model sejarawan kecil, (2) to analyze the development process of learning model sejarawan kecil based on the local history of Kasunanan Surakarta palace, (3) to know the feasibility of learning model sejarawan kecil based on the results of validation by model experts. The research method used in this research is Research and Development (R&D) with a qualitative approach, which is grouped into two stages: preliminary study and development study. The result of this research indicates that (1) the learning models that teachers use in history lessons at X grade of MAN 1 Surakarta are less varied because of limited knowledge about the procedure of innovative learning models; also, history learning that introduces students to the skills of history research that using local history never been used before. (2) In the development study, the design of the learning model sejarawan kecil based on the local history of Kasunanan Surakarta palace is validated internally by model experts and practitioners. (3) After passing the two stages of validation by model experts, the design of the learning model sejarawan kecil based on the local history of Kasunanan Surakarta palace has gained eligibility to be used on the field without revision.